Risk factors for neurosyphilis in HIV patients : A retrospective cohort study - Arns, Beatriz (2025)
Introduction: Syphilis is a highly prevalent sexually transmitted infection worldwide. Patients living with Human Immunodeficiency Virus (HIV) have a higher risk of developing neurosyphilis. Actual guidelines advise to proceed with lumbar puncture only if neurologic symptoms are present. However, asymptomatic neurosyphilis patients are not rare in the HIV population and other risk factors should be defined to guide screening. Methods: We performed a retrospective cohort to evaluate risk factors related to neurosyphilis in HIV patients. Adults with HIV infection and laboratory confirmed syphilis between 2011 and 2021 were included. Patients with no record of syphilis treatment, VDRL titers ≤ 1:4, other neurologic diseases or non-HIV related immunological impairment were excluded. The patients were followed for 2-years after syphilis diagnosis. Results: One-hundred and forty patients (190 syphilis episodes) were included, with mean age of 45.0 ± 9.2-years-old, 111 (79.3 %) were male, 48 (25.8 %) had CD4 count ≤ 350 cells/mm3 at syphilis diagnosis (median: 522.5 cells/mm3; IQR: 315.5‒703.5), 127 (66.8 %) of 172 had a HIV viral load ≤ 400 copies/mm3 and median serum VDRL titer was 1:64 (IQR: 1:16‒1:128). In multivariate analysis, serum VDRL titers ≥ 1:32 and the presence of neurologic symptoms were associated with neurosyphilis, while HIV viral load ≤ 400 copies/mm3 was a protective factor. Discussion: In addition to the presence of neurological symptoms, HIV viral load > 400 copies/mm3 and VDRL titers ≥ 1:32 were shown to be risk factors for neurosyphilis in this study and diagnostic lumbar puncture should be considered in these cases.